Direct measurements of ozone response to emissions perturbations in California - S. Wu; H. J. Lee; A. Anderson; A. Anderson; S. Liu; T. Kuwayama; J. H. Seinfeld; M. J. Kleeman (Atmospheric Chemistry and Physics, 2022)
A new technique was used to directly measure O3 response to changes in precursor NOx and volatile organic compound (VOC) concentrations in the atmosphere using three identical Teflon smog chambers equipped with UV lights. One chamber served as the baseline measurement for O3 formation, one chamber added NOx, and one chamber added surrogate VOCs (ethylene, m-xylene, n-hexane). Comparing the O3 formation between chambers over a 3-hour UV cycle provides a direct measurement of O3 sensitivity to precursor concentrations. Measurements made with this system at Sacramento, California, between April–December 2020 revealed that the atmospheric chemical regime followed a seasonal cycle. O3 formation was VOC-limited (NOx-rich) during the early spring, transitioned to NOx-limited during the summer due to increased concentrations of ambient VOCs with high O3 formation potential, and then returned to VOC-limited (NOx-rich) during the fall season as the concentrations of ambient VOCs decreased and NOx increased. This seasonal pattern of O3 sensitivity is consistent with the cycle of biogenic emissions in California. The direct chamber O3 sensitivity measurements matched semi-direct measurements of HCHO/NO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="61pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="ca557c5c52657b78a658d1e3e3865184"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-4929-2022-ie00001.svg" width="61pt" height="14pt" src="acp-22-4929-2022-ie00001.png"/></svg:svg> ratios from the TROPOspheric Monitoring Instrument (TROPOMI) aboard the Sentinel-5 Precursor (Sentinel-5P) satellite. Furthermore, the satellite observations showed that the same seasonal cycle in O3 sensitivity occurred over most of the entire state of California, with only the urban cores of the very large cities remaining VOC-limited across all seasons. The O3-nonattainment days (MDA8 O3>70 ppb) have O3 sensitivity in the NOx-limited regime, suggesting that a NOx emissions control strategy would be most effective at reducing these peak O3 concentrations. In contrast, a large portion of the days with MDA8 O3 concentrations below 55 ppb were in the VOC-limited regime, suggesting that an emissions control strategy focusing on NOx reduction would increase O3 concentrations. This challenging situation suggests that emissions control programs that focus on NOx reductions will immediately lower peak O3 concentrations but slightly increase intermediate O3 concentrations until NOx levels fall far enough to re-enter the NOx-limited regime. The spatial pattern of increasing and decreasing O3 concentrations in response to a NOx emissions control strategy should be carefully mapped in order to fully understand the public health implications.